Gynandromorphs of New Zealand Austrosimulium spp. (Diptera: Simuliidae) - Craig, Douglas A.; Crosby, Trevor K. (Zootaxa, 2008)
Investigations in the 1970s of Leucocytozoon tawaki Fallis, Bisset & Allison, a blood parasite of New Zealand’s Fiordland Crested Penguins (Eudyptes pachyrhynchus Gray) parasites normally transmitted by female simuliids resulted in the trapping of some 20 thousand female Austrosimulium (Austrosimulium) adults, attracted to captive penguins. Three species were involved: Austrosimulium (A.) australense (Schiner), A. (A.) dumbletoni Crosby and A. (A.) ungulatum Tonnoir. Of those adults trapped, 24 were gynandromorphs; one other was obtained from elsewhere. Austrosimulium dumbletoni has only its female adult described; the two other species have all their stages known. Eight gynandromorphs of A. dumbletoni have been identified and elsewhere will be used formally to describe, for the first time, the male of this species. Here, synoptic descriptions of the gynandromorphs are provided.